2020
DOI: 10.17509/jpjo.v5i1.22531
|View full text |Cite
|
Sign up to set email alerts
|

The Implementation of Problem Based Learning Model in Improving Cooperation and Learning Outcomes in Physical Education

Abstract: The decline in the culture of cooperation has an impact on the decrease of the student learning outcomes. The purpose of this study was to see the increase of critical thinking skill and cooperation in Physical Education and Health students through Problem Based Learning Model in Physical Education learning. The method used in this study was experimental method with the Randomize Pre-test and Post-test Control Group Design. The sampling technique in this study was cluster random sampling. The samples of this s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0
5

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 3 publications
0
15
0
5
Order By: Relevance
“…Selain itu, guru juga dituntut mampu meningkatkan motivasi belajar dan suasana belajar menyenangkan sehingga akan memudahkan siswa dalam belajar (Khan et al, 2019;Sun & Gao, 2016). Dalam menciptakan suasana belajar yang nyaman dan menyenangkan guru harus mampu menghadirkan situasi nyata dan mampu mendorong siswa untk membuat hubungan antara pengetahuan yang dimilikinya dengan penerapannya dalam kehidupan sehari-hari (Dupri et al, 2020;Sung, 2017). Hal ini juga dapat melatih siswa untuk belajar secara mandiri.…”
Section: Pendahuluanunclassified
“…Selain itu, guru juga dituntut mampu meningkatkan motivasi belajar dan suasana belajar menyenangkan sehingga akan memudahkan siswa dalam belajar (Khan et al, 2019;Sun & Gao, 2016). Dalam menciptakan suasana belajar yang nyaman dan menyenangkan guru harus mampu menghadirkan situasi nyata dan mampu mendorong siswa untk membuat hubungan antara pengetahuan yang dimilikinya dengan penerapannya dalam kehidupan sehari-hari (Dupri et al, 2020;Sung, 2017). Hal ini juga dapat melatih siswa untuk belajar secara mandiri.…”
Section: Pendahuluanunclassified
“…Previous research stated that audio-visual media could make it easier for students to understand learning materials (Fauzi et al, 2017;Michelsanti et al, 2019;Setiawan & Ari Oka, 2020). The findings of previous studies also stated that cooperative learning could increase students' enthusiasm and motivation to learn (Dupri et al, 2020;Gjems, 2013;Nurhusain, 2017). It can be concluded that cooperative learning with the aid of media will facilitate students in learning.…”
Section: Introductionmentioning
confidence: 96%
“…The cooperative learning model is a series of learning activities carried out by students in specific groups to achieve learning objectives (Nurhusain, 2017;Qusyairi & Sakila, 2018). Implementing the cooperative learning model will show learning activities to be effective (Dupri et al, 2020;Monica et al, 2017). In the cooperative learning model, there are five elements, namely: positive interdependence, individual responsibility, face to face, communication between members, and evaluation of group processes (Alfiani & Sopiyani, 2014;Diartini & Ratnawuri, 2017).…”
Section: Introductionmentioning
confidence: 99%
“…The quality of the success and success of Physical Education learning is strongly influenced by elements including teachers as the main element, students, curriculum, goals, methods, facilities and infrastructure, assessment, management, and classroom atmosphere (Gustiana & Puspita, 2020;Nur & Malik, 2021;Wang et al, 2021;Zhan et al, 2021). The success of the teaching and learning process of Physical Education is determined by several factors, namely internal factors and external factors (Dupri et al, 2020;Rokhayati et al, 2016;Rustiana, 2011;Wirasasmita & Hendriawan, 2020). Internal factors are teachers and physical education facilities and infrastructure as a tool to carry out teaching and learning activities in schools.…”
Section: Introductionmentioning
confidence: 99%